Purification, Molecular Docking and Cytotoxicity Evaluation of Bioactive Pentacyclic Polyhydroxylated Triterpenoids from Salvia urmiensis - Farimani, Mahdi Moridi; Abbas-Mohammadi, Mahdi; Ghorbannia-Dellavar, Samira; Nejad-Ebrahimi, Samad; Hamburger, Matthias (Planta Medica, 2024)
Triterpenoids, as one of the largest classes of naturally occurring secondary metabolites in higher plants, are of interest due to their high structural diversity and wide range of biological activities. In addition to several promising pharmacological activities such as antimicrobial, antiviral, antioxidant, anti-inflammatory and hepatoprotective effects, a large number of triterpenoids have revealed high potential for cancer therapy through their strong cytotoxicity on cancer cell lines and, also, low toxicity in normal cells. So, this study was aimed at discovering novel and potentially bioactive triterpenoids from the Salvia urmiensis species. For this, an ethyl acetate fraction of the acetone extract of the aerial parts of the plant was chromatographed to yield five novel polyhydroxylated triterpenoids (1–5). Their structure was elucidated by extensive spectroscopic methods including 1D (1H, 13C, DEPT-Q) and 2D NMR (COSY, HSQC, HMBC, NOESY) experiments, as well as HRESIMS analysis. Cytotoxic activity of the purified compounds was also investigated by MTT assay against the MCF-7 cancer cell line. Furthermore, a molecular docking analysis was applied to evaluate the inhibition potential of the ligands against the nuclear factor kappa B (NF-κB) protein, which promotes tumor metastasis or affects gene expression in cancer disease. The 1β,11β,22α-trihydroxy-olean-12-ene-3-one (compound 4) indicated the best activity in both in vitro and in silico assays, with an IC50 value of 32 µM and a docking score value of − 3.976 kcal/mol, respectively.
Keywords: MTT assay; structure elucidation; phytochemical; NMR; Salvia urmiensis; Lamiaceae